ANALISIS KINERJA PETUGAS AIRPORT SECURITY TERHADAP KEAMANAN PUBLIC AREA DI BANDAR UDARA INTERNASIONAL JENDERAL AHMAD YANI SEMARANG - Nuha Nadzifah (Jurnal Salome : Multidisipliner Keilmuan, 2024)
Public areas are public areas in airports. The airport security unit plays a role in maintaining security in this area. Maximum performance is an important aspect in order to meet work targets. In addition, it also provides a sense of security and comfort for airport service users. This research was carried out from August 6, 2023 to March 30, 2024. The research uses a descriptive qualitative method that collects data through observation, interviews, and documentation. The data is analyzed through the stages of data reduction, data presentation, and conclusion and verification. The validity of the data is carried out through triangulation of techniques and sources. The results of the study show that the performance of airport security officers is considered to be well implemented. However, there are several obstacles in the implementation of tasks such as limited communication tools, facilities, and the number of personnel. The solution sought is the use of alternative tools, the implementation of a rotation system, and regular coordination. Therefore, it is important for companies to improve the required work equipment as well as meet the needs of personnel.